VARIASI KALIMAT, PROPOSISI, DAN FUNGSI WACANA IKLAN MEDIA LUAR RUANG DI KOTA BANJARMASIN (VARIATION OF SENTENCES, PROPOSITIONS, AND DISCOURSE FUNCTIONS OF OUTDOOR MEDIA ADVERTISING IN BANJARMASIN CITY) - Rabiatul Sakban Miah (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
AbstractVariation of Sentences, Propositions, and Discourse Functions of Outdoor MediaAdvertising in Banjarmasin City. This study focuses on outdoor promotional media suchas banners, banners, billboards, posters, slogans, and trade name boards. This studyaims to describe the form of sentence variations based on their communicative function,describe the form of propositional advertising discourse, and show the functionscontained in outdoor media advertising discourse in Banjarmasin City. The approachused is a discourse approach with a descriptive qualitative research type and the use oflistening, reading, and note-taking methods. Sources of data in this study in the form ofoutdoor media in the city of Banjarmasin such as banners, banners, billboards, posters,slogans, and trade name boards. The data in this study are in the form of words andsentences listed in the discourse of outdoor media advertisements in the city ofBanjarmasin. The results of the study can be concluded that in the discourse of outdoormedia advertising in Banjarmasin City there are 33 data showing the use of declarativesentence variations, 1 data showing the use of interrogative sentence variations, and 3exclamative sentence data. In addition, there were also 16 data with propositions thatemphasized benefits for potential consumers, 20 data with propositions that aroused thecuriosity of potential consumers, and 1 data in the form of questions that demanded moreattention. The objective reason proposition was found as many as 28 data, the subjectivereason proposition 7 data, and mixed reasons of 2 data, as well as passive items as manyas 7 data.Key words: language functions, sentence variations, persuasion, advertisingpropositions, declarative AbstrakVariasi Kalimat, Proposisi, dan Fungsi Wacana Iklan Media Luar Ruang di KotaBanjarmasin. Penelitian ini berfokus pada media promosi luar ruang seperti spanduk,banner, baliho, poster, slogan, dan papan nama dagang. Penelitian ini bertujuan untukmendeskripsikan wujud variasi kalimat berdasar fungsi komunikatifnya, mendeskripsikanwujud proposisi wacana iklan, dan menunjukkan fungsi yang terkandung dalam wacanaiklan media luar ruang di Kota Banjarmasin. Pendekatan yang digunakan yaitupendekatan wacana dengan jenis penelitian kualitatif deskriptif serta penggunaan metodesimak, baca, dan catat. Sumber data pada penelitian ini berupa media luar ruang di kotaBanjarmasin seperti spanduk, banner, baliho, poster, slogan, dan papan nama dagang. Data dalam penelitian ini berupa kata-kata dan kalimat yang tercantum pada wacana iklanmedia luar ruang di kota Banjarmasin. Hasil penelitian dapat disimpulkan bahwa dalamwacana iklan media luar ruang di Kota Banjarmasin terdapat 33 data yang menunjukkanpenggunaan variasi kalimat deklaratif, 1 data menunjukkan penggunaan variasi kalimatintrogatif, dan 3 data kalimat ekslamatif. Selain itu juga ditemukan 16 data denganproposisi yang menekankan keuntungan bagi calon konsumen, 20 data dengan proposisiyang membangkitkan rasa ingin tahu kepada calon konsumen, dan 1 data berupapertanyaan yang menuntut perhatian lebih. Proposisi alasan objektif ditemukan sebanyak28 data, proposisi alasan subjektif 7 data, dan alasan campuran 2 data, serta butir pasifsebanyak 7 data.Kata-kata kunci: fungsi bahasa, variasi kalimat, persuasi, proposisi iklan, deklaratif